Parametric study on the thermoelectric conversion performance of a concentrated solar‐driven thermionic‐thermoelectric hybrid generator - Xiao, Lan; Wu, Shuang‐Ying; Yang, Shi‐Ling (International journal of energy research, 2018)
Summary A concentrated solar‐driven thermionic‐thermoelectric hybrid generator composed of solar heat collector, thermionic generator (TIG), thermoelectric generator (TEG), and radiator is introduced in this paper. A theoretical model of thermoelectric conversion performance for the hybrid generator is built up based on the heat source of the concentrated solar radiation rather than isothermal heat source. Based on the model, the impacts of related parameters on the internal temperature distributions, output power, and efficiency have been discussed. Moreover, the optimal operating conditions of the TIG‐TEG hybrid device at its maximum output power and efficiency have been determined. Results show that when cascading the TEG with the TIG, there is very little change of the TIG cathode temperature in most conditions, namely, TC ≈ TC′. Meanwhile, the anode temperature becomes higher, and the TEG cold end temperature T2 is close to the anode temperature TA′ for the single TIG system, ie, TA > TA′ ≈ T2. In theory, the optimal concentrated solar radiation I0 for the maximum output power Pmax and the maximum efficiency ηmax differs, which are I0,P = 2.5 × 106 W/m2 and I0,η = 2 × 106 W/m2, respectively, whereas the output power and efficiency of the TIG‐TEG hybrid system simultaneously reach their maximum values when the optimal TIG anode temperature TA,opt = 1025 K, the optimal TIG output voltage Vopt = 2 V, and the optimal ratio of load resistance to internal resistance (R2/R)opt = 2. However, in practice, the parameter values of I0, ΦA, and TA should be strictly controlled under 1.8 × 106 W/m2, 1.4 eV, and 660 K, respectively. Generally, the maximum output power and efficiency of the hybrid TIG‐TEG system are, respectively, 35% and 4% higher than that of the single TIG.